Analysis of Joint Destruction in Patients with Rheumatoid Arthritis Treated with Infliximab - ITO Satoshi; 坪井 洋人; 杉原 誠人; 鈴木 豪; 石井 亘; 千野 裕介; 真村 瑞子; 後藤 大輔; 松本 功; 堤 明人; 住田 孝之 (Japanese Journal of Rheumatism and Joint Surgery, 2007)
Objective: To assess the effect of infliximab (IFX) on joint destruction in patients with rheumatoid arthritis (RA) .Methods: We evaluated changes in X-ray images of the hands and feet of RA patients treated with IFX for at least one year. Twenty-five cases (10 males and 15 females) were evaluated. The mean age and disease duration were 52.2 ± 12.1 (range: 25-66) and 9.6 ± 6.3 (range: 1.7-24) years, respectively. The distributions of Steinbrocker's stage and class were I : 2, II : 10, III: 4, IV: 9 and 1: 10, 2: 10, 3: 4, 4: 2 respectively, and the American College of Rheumatology (ACR) responses were ACR 0×9, ACR 20×5, ACR 50×4, ACR 70×7 at one year. We evaluated the hands of one patient by compact magnetic resonance imagines (cMRI) before and after IFX treatment (6 times, 30 weeks) .Results: No worsening was observed in 20 cases (80.0%) in the hands and in 22 cases (88.0%) in the feet. After 1.5, 2 and 2.5 years, 7 (63.6%) and 8 (72.7%) cases out of 11, 3 (37.5%) and 5 (62.5%) cases out of 8, and 1 (16.7%) and 4 (66.7%) cases out of 6, respectively, did not exhibit worsening in the hands and feet respectively. Six cases showed worsening after one year, with ACR responses of ACR 0×1, ACR 20×1, ACR 50×3, and ACR 70×1. In the case examined by cMRI, erosions had improved dramatically.Conclusion: IFX appears to prevent joint destruction to some extent. Joint destruction may not be related to the ACR response, and further analysis using cMRI is required to assess this possibly.